1992
DOI: 10.1021/bi00120a003
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomerism of endothelin in acidic aqueous media: a quantitative NOESY analysis

Abstract: The conformational features of endothelin-1 (ET-1) in mixed water/ethylene glycol media have been studied by two-dimensional 1H NMR experiments throughout the pH range 3.2-7.2. At pH less than 5 all backbone NH signals can be observed, and NOESY experiments provided a large set of dipolar cross-peaks. Cross-peak intensities from each experiment (different mixing times and H2O versus D2O) were converted to distance constraints using a novel algorithm (program DISCON) for removing spin diffusion effects and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
85
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 57 publications
10
85
0
Order By: Relevance
“…[32][33][34][35][36] Because of its two intra-peptide disulfide bonds, ET1 has a compact tertiary structure in solution. In both the NMR [37][38][39] and X-ray 40 structures, the N-terminal region of ET1 adopts a somewhat distorted strand and the middle region forms a helix. This strand and helix are tightly linked by the disulfide bonds, constituting a cystine-stabilized helical (CSH) motif.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] Because of its two intra-peptide disulfide bonds, ET1 has a compact tertiary structure in solution. In both the NMR [37][38][39] and X-ray 40 structures, the N-terminal region of ET1 adopts a somewhat distorted strand and the middle region forms a helix. This strand and helix are tightly linked by the disulfide bonds, constituting a cystine-stabilized helical (CSH) motif.…”
Section: Introductionmentioning
confidence: 99%
“…A direct function at the receptor level, involving a disulfide exchange mechanism, has even been proposed for the exterior bridge (Spinella et al, 1991). Conformational studies agree that the central core of ET and possibly the segment 9 -21 adopts a helical organization (Endo et al, 1989;Saudek et al, 1989;Perkins et al, 1990;Aumelas et al, 1991;Andersen et al, 1992;Wallace & Janes, 1995;Orry & Wallace, 2000). This secondary structure would be stabilized by the cystine residues (Heitz et al, 1999) and would be, for instance, characterized by the alignment of the Tyr 13 and His 16 side chains (Orry & Wallace, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, structural analyses using circular dichroism or nuclear magnetic resonance (NMR) spectroscopies, as well as X-ray crystallography, have described, for instance, an a-helical arrangement located between residues 9 and 15 (or 16) (Endo et al, 1989;Saudek et al, 1989;Perkins et al, 1990;Aumelas et al, 1991;Andersen et al, 1992;Wallace & Janes, 1995;Katahira et al, 1998;Van Der Walle & Barlow, 1998;Boulanger et al, 1999;Hewage et al, 1999;Orry & Wallace, 2000;Hewage et al, 2002). Furthermore, some of these studies have reported that the helical backbone would be stabilized by hydrogen bonds involving more particularly the amino-acid pairs Lys 9 -Tyr 13 and Glu 10 -Phe…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following study, the 3D structure of these two antagonists are predicted, and the resulting models are then compared against the various solution structures for ET-1 that have been determined by means of 2D NMR and distance geometry calculations [17][18][19]. On the basis of these analyses a possible structural determinant of ET-A receptor binding is identified, and novel peptide designs are proposed for consideration as synthetic ET-A receptor antagonists.…”
Section: Introductionmentioning
confidence: 99%